P2X3 receptor antagonism attenuates the progression of heart failure - Renata M. Lataro; Davi J. A. Moraes; Fabio N. Gava; Ana C. M. Omoto; Carlos A. A. Silva; Fernanda Brognara; Lais Alflen; Vânia Brazão; Rafaela Pravato Colato; José Clóvis do Prado; Anthony P. Ford; Helio C. Salgado; et al. (Nature Communications, 2023)
Despite medications, heart failure worsens with time with many patients dying within five years of diagnosis. Here the authors show that blocking purinergic receptors in the carotid body stops heart failure progression, improves its function, reduces sleep apneas and systemic inflammation in male rats.